Rapid distributed processing of medium velocity geospatial datastreams into contextualised 3D visualisations : evaluating the cloud computing paradigm - Coetzee, Serena Martha (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2015.